Time of gold: the importance of promoting breastfeeding in the newborn's first hour of life (Research, Society and Development, 2022)
Objective: To report the importance and benefits associated with breastfeeding in the newborn's first hour of life. Methodology: The referent research is an integrative review. As inclusion criteria, the search period from 2015 to August 2021 was carried out, articles available in English and Portuguese, availability of free full text, and the search was carried out in the PUBMED, BIREME, SCIELO and CAPES databases. Publications that do not qualify as a scientific article were excluded from the research, for example, editorials and themes of the study that differed from the one addressed in this research. Results: 538 articles were found in the databases, 110 were excluded because they were duplicates, 60 were chosen by reading the title, of these selected, 31 presented a suggestive summary and similar to the choice of topic. Finally, an integral reading of the 31 studies was carried out, on an electronic screen, and it was evaluated that 18 of these articles were related to the importance of promoting breastfeeding in the newborn's first hour of life, being chosen to compose the integrative review. Conclusion: With this study, the importance and benefits of breastfeeding in the newborn's first hour of life is evident, with the family support network and humanized and quality care being essential.